An Analysis on the Language Style of the Utterances in Magnum Advertisements - Sonia Niken Permatasari; Made Frida Yulia (LLT Journal: A Journal on Language and Language Teaching, 2013)
The role of broadcasted advertisements is undeniably important for thecompanies to market their products. To convince the audience, advertisers have toconvey the persuasive message through the use of linguistic features. Those linguisticfeatures will influence the persuasion techniques used in advertisements and thepower relation which is built between the companies and the consumers.This study attempted to s olve two research problems related to the languagestyle of the utterances in Magnum advertisements. They were (1) What are thelinguistic features of Magnum advertisements? (2) What kind of power relation doesMagnum have upon consumers through the advertisements As an endeavor to solve those two problems, document analysis was employed in analyzing the transcript of the utterances in ten (10) Magnum advertisements. The first research problem was solved by categorizing the words or the sentencesinto some linguistic features of advertising language proposed by Grey (2008). Thesecond research problem was solved by interpreting the power relation in Magnumadvertisements based on Frenchs and Ravens theory (1959).From the obtained data, it was found that there were only a few linguisticfeatures which appeared in Magnum advertisements. The power relation betweenthe companies and the consumers could be defined easily because the utteranceswere clear enough. Furthermore, the simplicity of Magnum advertisements presentedMagnums special characteristics albeit the advertisers did not vary the languagestyle.